Concentric structure composite screw based on step-by-step antibacterial-vascularization-osteogenesis drug release system and preparation method of concentric structure composite screw
By designing a composite screw with a concentric structure, using a step-by-step antibacterial-vascular-osteogenic drug release system, the problem of unsatisfactory biological activity and mechanical strength in fracture treatment was solved, and efficient bone healing was achieved and anti-infection effects.
Patent Information
- Application Number
- CN202411302245.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-02-07
AI Technical Summary
Traditional screw materials have problems with unsatisfactory biological activity and mechanical strength in fracture treatment, and are prone to infection and slow bone healing after fracture.
A concentric structure composite screw based on the stepwise antibacterial-vascular-osynthetic drug release system was designed. Concentric circles were prepared by using AlgMA as the matrix and combined with multi-step in-situ casting-UV initial curing-freeze-demolding and other processes. The composite screws of the structure are arranged in the internal structure into an osteolayer, a vascular layer and an antibacterial layer in turn to achieve the sequential release of drugs.
The screw material exhibits excellent mechanical strength and anti-infection performance, and can release antibacterial, vascular and osteogenic drugs step by step, promote bone healing and significantly enhance the effectiveness of bone defect treatment.
Smart Images

Figure CN119386287A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation technology of screw materials, and in particular to a concentric structure composite screw based on a step-by-step antibacterial-angiogenic-osteogenic drug release system and a preparation method thereof. Background Art
[0002] Fracture is a very common disease in orthopedics, and the locking plate system is an important means of treating fracture. Currently, the locking plate systems used in clinical practice are mostly made of metal materials such as stainless steel or titanium alloy. Although fractures are not easy to occur, they still cannot meet the actual needs of patients due to problems such as stress shielding, non-degradability (requiring secondary surgery), and lack of biological activity.
[0003] In response to the problems of stress shielding and non-degradability, many scientists have prepared a series of polymer-based bone plate systems by using biodegradable biomedical materials such as chitosan and polylactic acid to simulate the strength of artificial bones, and overcome the defect of requiring a second surgery by virtue of the biodegradability of the materials. However, in view of the characteristics of fractures: 1) fractures are often prone to infection, especially at the contact surface of the bone plate and the screw; 2) the bone healing process after fracture is slow, which brings great inconvenience to patients. There is still a huge room for improvement in current materials.
[0004] In view of the above problems, the present invention designs a concentric structure composite screw based on a step-by-step antibacterial-angiogenic-osteogenic drug release system and a preparation method thereof. A composite screw with a concentric structure is prepared by using AlgMA as a matrix and combining a combination of multi-step in-situ casting-UV preliminary curing-freezing demoulding and other combined processes. The concentric structure provides the screw with excellent anti-bending performance; and the inside of the screw is sequentially arranged with an osteogenic layer-angiogenic layer-antibacterial layer from the inside to the outside, and sequential release is achieved through spatial physical steric hindrance, achieving the purpose of anti-infection and osteogenesis, which is of great significance for improving the treatment effect of bone defects. Summary of the invention
[0005] The purpose of the present invention is to provide a concentric structure composite screw based on a step-by-step antibacterial-angiogenic-osteogenic drug release system and a preparation method thereof in view of the problems of unsatisfactory biological activity and mechanical strength of traditional screw materials. The concentric circle structure and multi-layer space drug-loading structure of the screw of the present invention give it excellent mechanical strength and step-by-step antibacterial-angiogenic-osteogenic drug release ability, which has important clinical significance for the treatment of bone defects.
[0006] The present invention is implemented by the following technical solution, and the specific steps include:
[0007] A method for preparing a concentric structure composite screw based on a step-by-step antibacterial-angiogenic-osteogenic drug release system comprises the following steps:
[0008] 1) preparing three solutions, namely, methacryloyl sodium alginate (AlgMA) solutions loaded with antimicrobial drugs, angiogenic drugs, and osteogenic drugs;
[0009] 2) Designing and preparing a transparent step-by-step detachable casting mold with a concentric circle structure;
[0010] 3) Based on the mold and the three solutions, a composite pregel material having an osteogenic layer, angiogenic layer, and antibacterial layer from the inside to the outside is prepared by combining a multi-step in-situ casting-UV preliminary curing-freezing demoulding process;
[0011] 4) The composite pre-gel material is completely UV-cured to obtain a rod-shaped composite gel material, which is then dried by a rotary drying device to obtain a screw masterbatch, which is then turned according to the drawing to obtain a concentric structure composite screw material.
[0012] Furthermore, in step 1), the three solutions prepared all contain a photoinitiator, the substitution degree of AlgMA in the three solutions is 30-60%, and the concentration is 15-20wt%; the photoinitiator is one or more of LAP, Irgacure, and photoinitiator 2959, and the concentration is 0.25-0.5wt%; the antibacterial drug is one of silver nanoparticles and copper nanoparticles, and the concentration is 0.05-0.5wt%; the angiogenic drug is one or more of deferoxamine, salvianolic acid B, astragaloside, ginsenoside, and paeoniflorin, and the concentration is 0.5-2wt%; the osteogenic drug is one or more of nano-hydroxyapatite, bioactive glass, and nano-tantalum, and the concentration is 0.1-1.0wt%.
[0013] Furthermore, in step 1), during the preparation of the three solutions, the solutions are dissolved in a water bath at 60° C. under light-proof conditions, and ultrasound is used to assist drug dispersion.
[0014] Furthermore, the mold in step 2) includes: a base provided with concentric circular grooves and a detachable transparent hollow concentric cylindrical component, wherein the concentric circular grooves and the detachable transparent hollow concentric cylindrical component are provided in n numbers, wherein n is a multiple of 3;
[0015] The base has a diameter of 2-4 cm. Among the concentric circular grooves on the base, the innermost groove, i.e., the first layer, has a diameter of 3-5 mm, and the outermost groove, i.e., the nth layer, has a diameter of 2-4 cm. The grooves between the innermost and outermost layers are evenly spaced, and each concentric circular groove has a width of 0.3-0.5 mm and a depth of 2-5 mm.
[0016] The detachable transparent concentric cylindrical component is made of PMMA or PET, has a thickness consistent with the width of the groove, and a height of 10-20 cm.
[0017] Furthermore, the n is 9.
[0018] Further, in step 3), let i=1, during the multi-step in-situ casting-UV preliminary curing-freezing demoulding operation, insert the i-th layer of cylindrical components into the base groove of the mold, cast one of the solutions prepared in step 1) against the wall under light-proof conditions, use a hood-type ultraviolet lamp with a power of 20-30W and a wavelength of 405nm for UV preliminary curing for 5-10s, transfer the mold to a refrigerator for freezing demoulding and then i+1, and repeat the multi-step in-situ casting-UV preliminary curing-freezing demoulding operation; perform the multi-step in-situ casting-UV preliminary curing-freezing demoulding operation n times in total, and obtain a composite pregel material with an osteogenic layer, angiogenic layer, and antibacterial layer from the inside to the outside;
[0019] The solution is prepared in each pouring step 1) as follows: The first layer is AlgMA solution containing osteogenic drugs. The first layer is AlgMA solution containing angiogenic drugs. The first layer is AlgMA solution containing antibacterial drugs.
[0020] Furthermore, in step 4), during the UV complete curing process, a hood-type ultraviolet lamp is used with a wavelength of 405nm, a power of 20-30W, and a time of 10-15min.
[0021] Furthermore, the structure of the rotary drying equipment in step 4) is as follows: the heating and drying component is two heating screws arranged in parallel and juxtaposed and capable of rotating in opposite directions to each other, a stainless steel cylinder with fine holes is placed above the two screws for placing the sample to be dried, the screw speed is 20-50r / min, and the heating temperature is 50-80°C.
[0022] A concentric structure composite screw based on a step-by-step antibacterial-angiogenic-osteogenic drug release system is obtained by using any of the above-mentioned preparation methods.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] 1) The present invention uses AlgMA, antibacterial drugs, angiogenic drugs, osteogenic drugs, etc. as raw materials, and combines a combination of multi-step in-situ casting-UV preliminary curing-freezing demoulding, UV complete curing, rotary drying, turning and other combined processes to prepare a concentric structure composite screw material based on a step-by-step antibacterial-angiogenic-osteogenic drug release system. The above raw material selection and process combination are original to the present invention.
[0025] 2) Based on the operational requirements of multi-step in-situ casting, the present invention independently designed a transparent step-by-step detachable casting mold with a concentric circle structure. The multi-layer concentric circular components and detachable design of the above mold are developed according to the actual needs of the screw multi-layer concentric structure and different layers loaded with different drugs. The use of the above mold successfully realizes the step-by-step continuous preparation of rod-shaped composite gel materials, and also successfully realizes the controllable construction of the concentric structure of the material, providing feasibility for the preparation of the material.
[0026] 3) The composite screw material of the present invention has a concentric structure, and the osteogenic drugs, angiogenic drugs, and antibacterial drugs are sequentially loaded from the inside to the outside in the concentric structure layer, so that the material exhibits high bending strength, anti-infection, angiogenic and osteogenic properties. Among them, combined with the above-mentioned concentric circle structure and transparent step-by-step detachable casting mold, layer-by-layer casting and curing process, the concentric structure is successfully introduced into the screw. After drying and turning to obtain the finished screw, when the screw is broken by bending stress, the outer crack gradually develops to the inner layer, and the resistance of different stacks to the development of cracks can lead to the improvement of the bending strength of the material. On the other hand, since the concentric structure layer itself has an arrangement of internal and external physical spaces, when it is used, the outer layer is first in contact with the external tissue fluid, so the antibacterial drugs in the outer layer will be released first to achieve the prevention and treatment of surrounding infections; then the angiogenic drugs will be released in the second stage, preferentially promoting the repair of blood vessels in the bone defect area, providing good blood supply for subsequent osteogenesis, and the time of angiogenesis in the natural bone repair process is in the early stage of osteogenesis, matching it; finally, the osteogenic drugs on the inside are released to promote the formation of new bones. The above-mentioned prevention and treatment of infection, as well as the spatiotemporal promotion of angiogenesis and osteogenesis, provide important feasible strategies for the functional upgrading of traditional bone screws.
[0027] 4) In the present invention, AlgMA is selected as the raw material of the screw matrix. Through its UV curable and freeze-release characteristics, the matrix is matched with the application of a transparent step-by-step detachable casting mold with a concentric structure, thereby realizing the preparation of screws with a concentric structure. In terms of the selection of functional raw materials, we selected nanosilver / nanocopper as antibacterial drugs, hydroxyapatite, active glass, etc. as osteogenic drugs. Because anti-infection and osteogenic drugs are long-term processes, the above-mentioned stable inorganic substances are selected as active components. Through the long-term degradation of the above-mentioned components, the purpose of long-term effect can be achieved; as for the promotion of blood vessels, we selected deferoxamine, salvianolic acid B, astragaloside, ginsenoside, paeoniflorin and other small molecule drugs, which can play a role through molecular diffusion and meet the needs of blood vessels in the early stage of bone repair. The selection of the above raw materials is carefully determined according to the functional requirements of the materials of the present invention, and has obvious innovation. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1The present invention is a schematic diagram of the preparation process of a concentric structure composite screw material based on a step-by-step antibacterial-angiogenic-osteogenic drug release system according to an embodiment of the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described below with reference to specific examples.
[0030] Comparative Example 1:
[0031] 1) Selecting AlgMA with a substitution degree of 60%, using LAP as a photoinitiator, preparing a 15wt% AlgMA / 0.25wt% LAP solution under light-proof conditions and 60° C., adding 0.10wt% nanosilver, 0.5wt% deferoxamine and 0.3wt% hydroxyapatite composite AlgMA solution to the above solution, and using an ultrasonic process to assist dispersion;
[0032] 2) The above solution is poured into a transparent PMMA cylindrical mold (diameter 3.3 cm, height 10 cm), and completely UV cured (the ultraviolet lamp is hood-shaped, the wavelength is 405 nm, the power is 20 W, and the time is 15 min) to obtain a rod-shaped composite gel material, and then placed in a rotary drying device (the heating and drying components are two rotatable heating screws, and the two screw bodies are provided with stainless steel cylinders with fine holes) for drying (screw speed is 30 r / min, heating temperature is 60°C) to obtain a screw masterbatch, and the desired composite screw material is obtained after turning according to the drawing.
[0033] The extract of the above materials was prepared, and the cell survival rate was about 89.3% after co-culture with bone marrow mesenchymal stem cells (BMSCs) for 7 days; the bending strength of the bone nail was about 183.6MPa after the three-point bending test of the universal testing machine; the circular piece with a diameter of 1cm was cut from the cross-section direction for in vitro antibacterial zone test, and the antibacterial zone area was about 2.46cm 2 .
[0034] Embodiment 1:
[0035] 1) Selecting AlgMA with a substitution degree of 60%, using LAP as a photoinitiator, preparing a 15wt% AlgMA / 0.25wt% LAP solution under light-proof conditions and 60° C., adding 0.10wt% nanosilver to obtain an AlgMA solution loaded with anti-infective drugs, adding 0.5wt% deferoxamine to obtain an AlgMA solution loaded with angiogenic drugs, and adding 0.3wt% hydroxyapatite to obtain an AlgMA solution loaded with osteogenic drugs, and all the above three solutions are dispersed with the assistance of an ultrasonic process;
[0036] 2) Design and prepare a transparent step-by-step detachable casting mold with a concentric circle structure: the mold consists of a base with 9 concentric circular grooves and 9 detachable transparent concentric circular components. The base has a diameter of 3.3 cm, and the innermost groove of the inner concentric circular groove, i.e., the first layer, has a diameter of 3 mm, and the outermost groove, i.e., the ninth layer, has a diameter of 3.3 cm. The middle 7 grooves are evenly spaced, with a groove width of 0.3 mm and a depth of 3 mm. The detachable transparent concentric circular component is made of PMMA, with a thickness consistent with the width of the above groove and a height of 10 cm.
[0037] 3) Based on the above mold, combined with a multi-step in-situ casting-UV preliminary curing-freezing demoulding process (first, the innermost circular component, i.e., the first layer, is inserted on the base of the above mold, and the AlgMA solution containing the osteogenic drug is cast against the wall under light-proof conditions, and a hood-type ultraviolet lamp with a power of 20 W and a wavelength of 405 nm is used for UV preliminary curing for 5 seconds, and the mold is transferred to a -80°C refrigerator for freezing demoulding; the above operation is repeated 8 times, and a circular component with a gradually increasing diameter is inserted each time, and the solution poured each time is changed accordingly depending on the number of layers, specifically: from the inside to the outside, 1-3 layers are AlgMA solutions containing osteogenic drugs, 4-6 layers are AlgMA solutions containing angiogenic drugs, and 7-9 layers are AlgMA solutions containing antibacterial drugs), a composite pregel material with an osteogenic layer, angiogenic layer, and antibacterial layer from the inside to the outside is obtained;
[0038] 4) The pre-gel is completely UV-cured (the UV lamp is in a hood shape, with a wavelength of 405 nm, a power of 20 W, and a time of 15 min) to obtain a rod-shaped composite gel material, and the rod-shaped composite gel material is placed in a stainless steel cylinder of a rotary drying device (the heating and drying components are two rotatable heating screws, and the two screw bodies are provided with stainless steel cylinders with fine holes) for drying (the screw speed is 30 r / min, and the heating temperature is 60°C) to obtain a screw masterbatch, which is then turned according to the drawing to obtain the desired composite screw material.
[0039] Compared with the comparative example, this embodiment introduces a transparent step-by-step detachable casting mold with a concentric structure, and divides the above-mentioned osteogenic layer, angiogenic layer, and antibacterial layer into 9 layers from the inside to the outside for casting, thereby obtaining a new composite screw material with a concentric structure and different spatial distributions of drugs. The extract of the above-mentioned material was prepared, and the cell survival rate was about 92.4% after co-culture with bone marrow mesenchymal stem cells (BMSCs) for 7 days; the bending strength of the bone screw after the three-point bending test of the universal testing machine was about 359.8MPa; a disc with a diameter of 1cm was cut from the cross-section direction for in vitro antibacterial zone detection, and the antibacterial zone area was about 3.15cm 2 .
[0040] Embodiment 2:
[0041] 1) Selecting AlgMA with a substitution degree of 60%, using LAP as a photoinitiator, preparing a 15wt% AlgMA / 0.25wt% LAP solution under light-proof conditions and 60° C., adding 0.10wt% nanosilver to obtain an AlgMA solution loaded with anti-infective drugs, adding 0.5wt% deferoxamine to obtain an AlgMA solution loaded with angiogenic drugs, and adding 0.3wt% hydroxyapatite to obtain an AlgMA solution loaded with osteogenic drugs, and all the above three solutions are dispersed with the assistance of an ultrasonic process;
[0042] 2) Design and prepare a transparent step-by-step detachable casting mold with a concentric circle structure: the mold consists of a base with 9 concentric circular grooves and 9 detachable transparent concentric circular components. The base has a diameter of 3.3 cm, and the innermost groove of the inner concentric circular groove, i.e., the first layer, has a diameter of 3 mm, and the outermost groove, i.e., the ninth layer, has a diameter of 3.3 cm. The middle 7 grooves are evenly spaced, with a groove width of 0.3 mm and a depth of 3 mm. The detachable transparent concentric circular component is made of PMMA, with a thickness consistent with the width of the above groove and a height of 10 cm.
[0043] 3) Based on the above mold, combined with a multi-step in-situ casting-UV preliminary curing-freezing demoulding process (first insert the third circular component from the inside to the outside on the base of the above mold, cast the AlgMA solution containing the osteogenic drug against the wall under light-proof conditions, use a hood-type ultraviolet lamp with a power of 20W and a wavelength of 405nm for UV preliminary curing for 5s, and transfer the mold to a -80°C refrigerator for freezing demoulding; repeat the above operation twice (i.e., insert the sixth and ninth circular components in sequence), and the solution poured each time changes accordingly depending on the number of layers, specifically: the first layer composed of the third cylindrical component from the inside to the outside is the AlgMA solution containing the osteogenic drug, the second layer composed of the sixth cylindrical component is the AlgMA solution containing the angiogenic drug, and the third layer composed of the ninth cylindrical component is the AlgMA solution containing the antibacterial drug), to obtain a composite pregel material having an osteogenic layer-angiogenic layer-antibacterial layer from the inside to the outside;
[0044] 4) The pre-gel is completely UV-cured (the UV lamp is in a hood shape, with a wavelength of 405 nm, a power of 20 W, and a time of 15 min) to obtain a rod-shaped composite gel material, and the rod-shaped composite gel material is placed in a stainless steel cylinder of a rotary drying device (the heating and drying components are two rotatable heating screws, and the two screw bodies are provided with stainless steel cylinders with fine holes) for drying (the screw speed is 30 r / min, and the heating temperature is 60°C) to obtain a screw masterbatch, which is then turned according to the drawing to obtain the desired composite screw material.
[0045] Compared with Example 1, this example reduces the 9-layer concentric structure to 3 layers, that is, the solutions of the same active drug components are combined into a single layer. The extract of the above materials was prepared, and the cell survival rate was about 90.4% after co-culture with bone marrow mesenchymal stem cells (BMSCs) for 7 days; the bending strength of the bone nail after the three-point bending test of the universal testing machine was about 236.8MPa; the circular piece with a diameter of 1cm was cut from the cross-section direction for in vitro antibacterial zone detection, and the antibacterial zone area was about 3.47cm 2 .
[0046] Embodiment 3:
[0047] 1) Selecting AlgMA with a substitution degree of 60%, using LAP as a photoinitiator, preparing a 20wt% AlgMA / 0.5wt% LAP solution under light-proof conditions and 60° C., adding 0.10wt% nanosilver to obtain an AlgMA solution loaded with anti-infective drugs, adding 0.5wt% deferoxamine to obtain an AlgMA solution loaded with angiogenic drugs, and adding 0.3wt% hydroxyapatite to obtain an AlgMA solution loaded with osteogenic drugs, and all the above three solutions are dispersed with the assistance of an ultrasonic process;
[0048] 2) Design and prepare a transparent step-by-step detachable casting mold with a concentric circle structure: the mold consists of a base with 9 concentric circular grooves and 9 detachable transparent concentric circular components. The base has a diameter of 3.3 cm, and the innermost groove of the inner concentric circular groove, i.e., the first layer, has a diameter of 3 mm, and the outermost groove, i.e., the ninth layer, has a diameter of 3.3 cm. The middle 7 grooves are evenly spaced, with a groove width of 0.3 mm and a depth of 3 mm. The detachable transparent concentric circular component is made of PMMA, with a thickness consistent with the width of the above groove and a height of 10 cm.
[0049] 3) Based on the above mold, combined with a multi-step in-situ casting-UV preliminary curing-freezing demoulding process (first, the innermost circular component, i.e., the first layer, is inserted on the base of the above mold, and the AlgMA solution containing the osteogenic drug is cast against the wall under light-proof conditions, and a hood-type ultraviolet lamp with a power of 20 W and a wavelength of 405 nm is used for UV preliminary curing for 5 seconds, and the mold is transferred to a -80°C refrigerator for freezing demoulding; the above operation is repeated 8 times, and a circular component with a gradually increasing diameter is inserted each time, and the solution poured each time is changed accordingly depending on the number of layers, specifically: from the inside to the outside, 1-3 layers are AlgMA layers containing osteogenic drugs, 4-6 layers are AlgMA layers containing angiogenic drugs, and 7-9 layers are AlgMA layers containing antibacterial drugs), a composite pregel material with an osteogenic layer, angiogenic layer, and antibacterial layer from the inside to the outside is obtained;
[0050] 4) The pre-gel is completely UV-cured (the UV lamp is in a hood shape, with a wavelength of 405 nm, a power of 20 W, and a time of 15 min) to obtain a rod-shaped composite gel material, and the rod-shaped composite gel material is placed in a stainless steel cylinder of a rotary drying device (the heating and drying components are two rotatable heating screws, and the two screw bodies are provided with stainless steel cylinders with fine holes) for drying (the screw speed is 30 r / min, and the heating temperature is 60°C) to obtain a screw masterbatch, which is then turned according to the drawing to obtain the desired composite screw material.
[0051] Compared with Example 1, the concentration of AlgMA is increased in this example. The extract of the above materials was prepared, and the cell survival rate was about 94.9% after co-culture with bone marrow mesenchymal stem cells (BMSCs) for 7 days; the bending strength of the bone nail after the three-point bending test of the universal testing machine was about 391.1MPa; a disc with a diameter of 1cm was cut from the cross-section direction for in vitro antibacterial zone detection, and the antibacterial zone area was about 3.02cm 2 .
Claims
1. A method for preparing a concentric structure composite screw based on a step-by-step antibacterial-angiogenic-osteogenic drug release system, characterized in that: The following steps are involved: 1) preparing three solutions, namely, methacryloyl sodium alginate (AlgMA) solutions loaded with antimicrobial drugs, angiogenic drugs, and osteogenic drugs; 2) Designing and preparing a transparent step-by-step detachable casting mold with a concentric circle structure; 3) Based on the mold and the three solutions, a composite pregel material having an osteogenic layer, angiogenic layer, and antibacterial layer from the inside to the outside is prepared by combining a multi-step in-situ casting-UV preliminary curing-freezing demoulding process; 4) The composite pre-gel material is completely UV-cured to obtain a rod-shaped composite gel material, which is then dried by a rotary drying device to obtain a screw masterbatch, which is then turned according to the drawing to obtain a concentric structure composite screw material.
2. The method for preparing a concentric structure composite screw based on a stepwise antibacterial-angiogenic-osteogenic drug release system according to claim 1, characterized in that: In step 1), the three solutions prepared all contain a photoinitiator, the substitution degree of AlgMA in the three solutions is 30-60%, and the concentration is 15-20wt%; the photoinitiator is one or more of LAP, Irgacure, and photoinitiator 2959, and the concentration is 0.25-0.5wt%; the antibacterial drug is one of silver nanoparticles and copper nanoparticles, and the concentration is 0.05-0.5wt%; the angiogenic drug is one or more of deferoxamine, salvianolic acid B, astragaloside, ginsenoside, and paeoniflorin, and the concentration is 0.5-2wt%; the osteogenic drug is one or more of nano-hydroxyapatite, bioactive glass, and nano-tantalum, and the concentration is 0.1-1.0wt%.
3. The method for preparing a concentric structure composite screw based on a stepwise antibacterial-angiogenic-osteogenic drug release system according to claim 1, characterized in that: In step 1), during the preparation of the three solutions, the solutions were dissolved in a water bath at 60° C. under light-proof conditions, and ultrasound assisted drug dispersion.
4. The method for preparing a concentric structure composite screw based on a stepwise antibacterial-angiogenic-osteogenic drug release system according to claim 1, characterized in that: The mold in step 2) comprises: a base provided with concentric circular grooves and a detachable transparent hollow concentric cylindrical component, wherein the concentric circular grooves and the detachable transparent hollow concentric cylindrical component are provided in n numbers, wherein n is a multiple of 3 and n is greater than 3; The base has a diameter of 2-4 cm. Among the concentric circular grooves on the base, the innermost groove, i.e., the first layer, has a diameter of 3-5 mm, and the outermost groove, i.e., the nth layer, has a diameter of 2-4 cm. The grooves between the innermost and outermost layers are evenly spaced, and each concentric circular groove has a width of 0.3-0.5 mm and a depth of 2-5 mm. The detachable transparent concentric cylindrical component is made of PMMA or PET, has a thickness consistent with the width of the groove, and a height of 10-20 cm.
5. The method for preparing a concentric structure composite screw based on a step-by-step antibacterial-angiogenic-osteogenic drug release system according to claim 4, characterized in that: The n is 9.
6. The method for preparing a concentric structure composite screw based on a step-by-step antibacterial-angiogenic-osteogenic drug release system according to claim 4, characterized in that: In step 3), i=1 is set, and during the multi-step in-situ casting-UV preliminary curing-freezing demoulding operation, the cylindrical component of the i-th layer is inserted into the base groove of the mold, and one of the solutions prepared in step 1) is cast against the wall under light-proof conditions, and UV preliminary curing is performed for 5-10 seconds using a hood-type ultraviolet lamp with a power of 20-30W and a wavelength of 405nm. The mold is transferred to a refrigerator for freezing demoulding and then i+1, and the multi-step in-situ casting-UV preliminary curing-freezing demoulding operation is repeated; the multi-step in-situ casting-UV preliminary curing-freezing demoulding operation is performed n times in total to obtain a composite pregel material having an osteogenic layer, angiogenic layer, and antibacterial layer from the inside to the outside; The solution is prepared in each pouring step 1) as follows: The first layer is AlgMA solution containing osteogenic drugs. The first layer is AlgMA solution containing angiogenic drugs. The first layer is AlgMA solution containing antibacterial drugs.
7. The method for preparing a concentric structure composite screw based on a stepwise antibacterial-angiogenic-osteogenic drug release system according to claim 1, characterized in that: In step 4), during the UV complete curing process, a hood-type ultraviolet lamp is used with a wavelength of 405nm, a power of 20-30W, and a time of 10-15min.
8. The method for preparing a concentric structure composite screw based on a stepwise antibacterial-angiogenic-osteogenic drug release system according to claim 1, characterized in that: The structure of the rotary drying equipment in step 4) is as follows: the heating and drying component is two parallel and juxtaposed heating screws that can rotate in opposite directions. A stainless steel cylinder with fine holes is placed above the two screws for placing the sample to be dried. The screw speed is 20-50r / min and the heating temperature is 50-80°C.
9. A concentric composite screw based on a progressive antibacterial-angiogenic-osteogenic drug release system, characterized in that: The method is adopted as described in any one of claims 1 to 8.
Citation Information
Cited By
In-situ adhesion gel filler with biofilm attacking and dual osteogenesis promoting functions as well as preparation method and application of in-situ adhesion gel filler
CN121288013A